Ghrelin: A link between memory and ingestive behavior - Hsu, Ted M. (Physiol Behav, 2016)
Feeding is a highly complex behavior that is influenced by learned associations between external and internal cues. The type of excessive feeding behavior contributing to obesity onset and metabolic deficit may be based, in part, on conditioned appetitive and ingestive behaviors that occur in response to environmental and/or interoceptive cues associated with palatable food. Therefore, there is a critical need to understand the neurobiology underlying learned aspects of feeding behavior. The stomach-derived “hunger” hormone, ghrelin, stimulates appetite and food intake and may function as an important biological substrate linking mnemonic processes with feeding control. The current review highlights data supporting a role for ghrelin in mediating the cognitive and neurobiological mechanisms that underlie conditioned feeding behavior. We discuss the role of learning and memory on food intake control (with a particular focus on hippocampal-dependent memory processes) and provide an overview of conditioned cephalic endocrine responses. A neurobiological framework is provided through which conditioned cephalic ghrelin secretion signals in neurons in the hippocampus, which then engage orexigenic neural circuitry in the lateral hypothalamus to express learned feeding behavior.